Pharmacomicrobiomics in inflammatory skin diseases: past, present, and the future - Khang, Juna; Martinez, Rebeca; Brag, Katherine; McGee, Jean S. (Frontiers in Microbiology, 2026)
This mini review article focuses on pharmacomicrobiomics, or the study of how the composition and activity of microorganisms in the body, in particular in the gut, impact drug pharmacokinetics and pharmacodynamics. This evolving field has profound implications for personalized medicine in the management of chronic inflammatory diseases. Particularly in dermatology, patient response to an expanding collection of biologic and small molecule inhibitor therapies coming out on the market remains unpredictable. The decision to start which therapy depends on physician preference, rather than based on what is expected to be the treatment response of each individual. This therapeutic uncertainty leads to sequential treatment failures, increased patient morbidity, and substantial healthcare expenditure. This mini-review synthesizes the evidence surrounding the gut microbiome as a predictive biomarker for therapeutic response in inflammatory skin diseases. We will examine the past use of pharmacomicrobiomics in oncology, where gut microbial signatures were found to predict response to immunotherapy in melanoma. We then analyze the present, focusing on the robust translational models from inflammatory bowel disease (IBD) and rheumatoid arthritis (RA), and the established gut dysbiosis in dermatologic conditions such as psoriasis and hidradenitis suppurativa (HS). Finally, we consider the future, discussing the potential for microbiome-based diagnostics to guide therapy selection for chronic inflammatory skin diseases.